THE CHANGING FACE OF THAI TOURIST DECISION-MAKING AND, CONSUMPTION RESPONSES AND BEHAVIORAL CHANGES POST-COVID 19 - Hassan, Md Saif; Batra, Adarsh (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The global pandemic “COVID 19” has brought a huge contrast globally, creating a crisis by crippling the whole world, nations in it, and its living beings as well. Resulting in collapsing of the tourism sector, made many unemployed as well throughout the world in many countries. During this pandemic, many people are affected by a change in them either demographically, psychographically, or brought upon behavioral changes. Thailand itself was one of the countries to have the virus and once a tourism robust country went down within a month due to lockdowns and closing of airports, shopping malls, many restaurants, etc. Consumers got quite affected by this problem and tend to put fear inside consumers for them to travel back again. Therefore, this research aimed to understand the tourist nature of traveling post-COVID and it was important to understand consumers' feelings and expectations for consumers to travel back again. The research used mixed-method research, that is, qualitative and quantitative involving the non-probability convenience sampling method. In-depth interviews provided a wide range of feelings and understanding, and a short survey was distributed to understand further if qualitative data relates to the answers from an in-depth interview. Results were analyzed through thematic analysis, while overall survey results were just compared for further validity and assurance. Results, shown that the tourists believe the tourism sector for both outbound will be booming again but it all depends on the tour operators, government and the local community will act for it. This study will be helpful to for tour operators in terms of understanding the expectations, needs, and interests of consumers and what precautions should be taken to make Thai tourists travel either outbound or domestic again post.